The prevalence of metabolic syndrome among psychiatric inpatients in Brazil - Teixeira,Paulo José Ribeiro (2007)
OBJECTIVE: Metabolic syndrome is a highly prevalent disorder among the general population. Studies show an even higher prevalence among psychiatric patients. The objective of this study is to assess the prevalence of metabolic syndrome among inpatients of a psychiatric ward of a general hospital in Brazil and correlate it with their respective psychiatric diagnoses and with the antipsychotics and mood stabilizers used. METHOD: 170 inpatients (mean age: 45.6 years) were evaluated according to the National Cholesterol Education Program criteria for metabolic syndrome, with a modification of the criteria for blood pressure and fasting glucose. RESULTS: The prevalence found was 29.4%, being higher in women (43.6% versus 20.8%, p = 0.002). The prevalence stratified by psychiatric diagnostic was 48.1% for depression, 38.3% for bipolar disorder, 31.8% for schizophrenia and schizoaffective disorder, 5.1% for alcoholism, and 23.1% for "other mental disorders". The prevalence for alcoholism was significantly lower than the prevalence rates associated with other diagnostic categories (p = 0.035). After using the multivariate analysis, female gender and use of lithium remained as factors associated with a diagnosis of metabolic syndrome. CONCLUSIONS: The prevalence found was 29.4%. Gender (female) and use of lithium were factors significantly associated with the diagnosis of metabolic syndrome.